Relationships among rise, cup, roll and stagger in DNA suggested by empirical potential studies of base stacking - Sponer, J; Kypr, J (Journal of biomolecular structure & dynamics, 1993)
Empirical analyses of experimental data have recently revealed a strong correlation in B- and A-DNA crystal structures between rise of the base pair steps and their cup, or the difference between roll and cup. We show here using empirical potentials that a major part of this correlation can be explained by the base stacking forces. Our calculations further demonstrate that the correlation depends on the base sequence while the dependence is strongest with the C-G step. We also show that small values (which lie beyond resolution of the X-ray diffraction data obtained with the DNA fragment single crystals) of base pair stagger can completely substitute for the effects of roll in the correlation. The present and our previous studies demonstrate that the base pair buckle and stagger can substantially affect base stacking in DNA so that variability of these parameters cannot be neglected in the theoretical analysis of the base sequence effects on DNA conformation.
Keywords: zastoupení bazí; DNA; sekvence nukleotidů; oligodeoxyribonukleotidy; molekulární sekvence - údaje; konformace nukleové kyseliny; Base Sequence; Molecular Sequence Data; Nucleic Acid Conformation; X-Ray Diffraction; Crystallization; Oligodeoxyribonucleotides; difrakce rentgenového záření; krystalizace; Base Composition